Kinematische Tätigkeitsanalyse Identifikation von ruckbasierten Parametern zur Ermittlung der Anstrengung am Beispiel einer repetitiven Punkt-zu-Punkt Bewegung - Bringeland, Sabrina (Karlsruher Forschungsberichte zur Arbeitswissenschaft und Betriebsorganisation, 2022)
The assessment of perceived exertion is highly relevant for workplace design to improve the quality of work. This approach represents an objective method based on kinematic data. The method's objective was to determine the feasibility of using the time derivative of acceleration - jerk - as an indicator of time of increased physical exertion (TIPE). The result showed that the jerk data peaks' height and frequency are useful indicators for identifying physical exertion.